The Influence of Digital Economy, Digital Literacy, and Marketing Innovation on the Performance of Culinary MSMEs in Makassar - S., Ratnah; Arisah, Nur (International journal of technology and education research, 2025)
This study aims to explore the influence of the digital economy, digital literacy, and marketing innovation on the performance of culinary Micro, Small, and Medium Enterprises (MSMEs) in Makassar. Involving 120 culinary MSMEs, the study found that the use of digital platforms such as GoFood and GrabFood significantly increased sales turnover. Furthermore, good digital literacy, namely the ability to use technology and understand sales data, also contributes significantly to business success. Marketing innovations, such as the use of social media to promote products, have proven effective in attracting new customers and retaining existing ones. The results show that MSMEs that actively adapt to digital technology and implement creative marketing strategies can significantly improve their business performance. These findings provide important insights for MSMEs in Makassar to capitalize on opportunities in the digital era for the sustainability of their businesses